Estimation of Soil Erosion in Sefidrood Watershed by Emphasis on the Role of Landforms - Alireza Jafarzadeh Estalkhkouhi; Parviz Rezaei (تحقیقات کاربردی علوم جغرافیایی)
Among the various processes that destroy lands, soil erosion is a complex and hazardous environmental process that constitutes a serious threat to preservation of soil and water resources in Iran and has inflicted its negative effects on the vital ecosystem with the intensified utilization of nature by human beings. The present descriptive and analytic research employed the PSIAC model to study erosion and compare it with other empirical methods and models by investigating the effects of nine important and influential factors in soil erosion and sediment production in various parts of the Sefidrood Basin through giving intra-layer numerical scores to them. Erosion and landform zoning maps and also zoning maps for the nine factors were then extracted. Results indicated that 77 percent of the lands in the plain landforms faced very little erosion and 23 percent little erosion, 14 percent of the lands in the mountainside landforms were exposed to very high erosion rates, 55 percent with high erosion rates, and 31 percent with average and low erosion rates, and 17 percent of the lands in the mountain landforms experienced very high erosion rates, 58 percent high erosion rates, and 25 percent average erosion rates. In other words, the rates of erosion changed from low in the plain landforms to very high in the mountain landforms. This implies that pastures and natural resources are confronted with numerous problems. In general, considering the study carried out on the nine influential factors in the soil erosion model (the PSIAC model), we notice that the mountainside and mountainous regions are more sensitive to erosion and influential factors in erosion are more active in these regions.